Functional and Phenotypic Diversity of Microglia: Implication for Microglia-Based Therapies for Alzheimer’s Disease - Xu, Yi-Jun; Au, Ngan Pan Bennett; Ma, Chi Him Eddie (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease and is closely associated with the accumulation of β-amyloid (Aβ) and neurofibrillary tangles (NFTs). Apart from β-amyloid and NFT pathologies, AD patients also exhibit a widespread microglial activation in various brain regions with elevated production of pro-inflammatory cytokines, a phenomenon known as neuroinflammation. In healthy central nervous system, microglia adopt ramified, ‘surveying’ phenotype with compact cell bodies and elongated processes. In AD, the presence of pathogenic proteins such as extracellular Aβ plaques and hyperphosphorylated tau, induce the transformation of ramified microglia into amoeboid microglia. Ameboid microglia are highly phagocytic immune cells and actively secrete a cascade of pro-inflammatory cytokines and chemokines. However, the phagocytic ability of microglia gradually declines with age, and thus the clearance of pathogenic proteins becomes highly ineffective, leading to the accumulation of Aβ plaques and hyperphosphorylated tau in the aging brain. The accumulation of pathogenic proteins further augments the neuroinflammatory responses and sustains the activation of microglia. The excessive production of pro-inflammatory cytokines induces a massive loss of functional synapses and neurons, further worsening the disease condition of AD. More recently, the identification of a subset of microglia by transcriptomic studies, namely disease-associated microglia (DAM), the progressive transition from homeostatic microglia to DAM is TREM2-dependent and the homeostatic microglia gradually acquire the state of DAM during the disease progression of AD. Recent in-depth transcriptomic analysis identifies ApoE and Trem2 from microglia as the major risk factors for AD pathogenesis. In this review, we summarize current understandings of the functional roles of age-dependent microglial activation and neuroinflammation in the pathogenesis of AD. To this end, the exponential growth in transcriptomic data provides a solid foundation for in silico drug screening and gains further insight into the development of microglia-based therapeutic interventions for AD.